Pravda . Pravda . Truth . Правда - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing problems in the Russian press, in particular the newspaper Pravda. Featured in the program: Novodvorskaia, Valeriia Il'inichna (Politician); Ziuganov, Gennadii Andreevich (Deputy of the State Duma) Contributors: TPO obshchestvenno-politicheskikh programm (Studio) Обсуждение проблем российской прессы, в частности, газеты Правда. В программе участвуют: Новодворская, Валерия Ильинична (Политик); Зюганов, Геннадий Андреевич (Депутат Государственной Думы) Создатели: ТПО общественно-политических программ (Студия)